Persepsi guru-guru sekolah rendah terhadap pengajaran dan pembelajaran Sains dan Matematik dalam Bahasa Inggeris di daerah Serian, Sarawak - Guncheng, anak Banter (2010)
The purpose of this study focuses on the perception of teachers toward the teaching of Sciences and Mathematics in English, in primary school in Serian district, Sarawak. This study examines the perception of teachers on training and courses given by the Ministery Of Education (MOE) dan problems encountered during the courses. This study also examines the perception made by teachers before class as well as difficulties encountered in teaching Sciences and Mathematics and the usage of English among the ETeMs teachers in their teaching. Respondents of this study consists 126 Sciences and Mathematics teachers who are randomly selected from 21 primary school in Serian district. The methodology used in this was a set of questionnaires and was analysis using descriptive statistics such as frequency, percentage and means. T-test, ANOVA and Correlation Pearson 'r' also used in this study to measured the relationship between 3 dimension. Pilot test also carried out to measure the reliability of the questionnaires. The result of pilot test shows significant with the cronbach alpha 0.876 (p> .05). Meaning that the questionnaires are valid and reliable for the actual study. Results of the study shows significant based on the 5 dimensions test. That is (1) perception on courses attended, mean 3.965, (2) difficulties during courses, mean 4.027, (3) preparation before class, mean 3.947, (4) difficulties using English in classroom, mean 4.340 and lastly, (5) perception on the usage of English as the main instruction for teaching and learning sciences and mathematics , mean shows 4.001. The result of the study as whole is significant. The result of the study was also answer the perception towards the implemention of ETeMS are not fare for schools in rural areas. The finding shows the respondents not agreed with that perception because the result is significant, meaning that the pupils in rural areas are already adapt the usage of English in learning both subjects and had their level of proficiency in English are better